PENERAPAN MODEL PEMBELAJARAN PROJECT-BASED LEARNING (PJBL) UNTUK MENINGKATKAN KEAKTIFAN PESERTA DIDIK PADA MATA PELAJARAN EKONOMI - Nurul Farahdilla; Albrian Prakoso; Nurul Fahimah (Jurnal Dedikasi Pendidikan, 2023)
In a learning process that runs well, it certainly involves the activeness of students. Activeness is an activity that involves both body and mind. The activeness of students in learning to emphasize understanding of the problems they will face in the learning process. Based on the results of interviews with economics teachers, it is known that there are problems during the learning process. Teachers do learning dominated by learning that is still teacher-centered, where the role of the teacher in the learning process is more than the role of students. Using the usual learning methods applied by the teacher, it appears that students are not actively involved in the learning process. Judging from these problems, innovations in learning models need to be made, one of which is a learning model that can make students active in the learning process. A suitable model to be practiced in increasing learning activeness is the project-based learning model. The research conducted is a class action research with the research subject is class XI IPS 2 SMA Negeri 3 Bojonegoro. The instrument used was an observation sheet. This study uses two cycles, the first cycle using a project-based learning model (PjBL) gets an average result of 54% classified in the good category, but has not reached the level of research success indicators that have been determined. In the second cycle, by applying the project-based learning model (PjBL), the results with an average of 86% were classified as very good and had reached the specified success indicators. Based on the results obtained, this indicates that this class action research (PTK) has been successful. the use of project-based learning models (PjBL) can increase the activeness of students in undergoing economic learning in class XI IPS 2 SMA Negeri 3 Bojonegoro on the material of international economic cooperation.